2021
DOI: 10.1093/brain/awab029
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging towards clinical application in multiple sclerosis

Abstract: Quantitative MRI provides biophysical measures of the microstructural integrity of the CNS, which can be compared across CNS regions, patients, and centres. In patients with multiple sclerosis, quantitative MRI techniques such as relaxometry, myelin imaging, magnetization transfer, diffusion MRI, quantitative susceptibility mapping, and perfusion MRI, complement conventional MRI techniques by providing insight into disease mechanisms. These include: (i) presence and extent of diffuse damage in CNS tissue outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 195 publications
0
93
0
2
Order By: Relevance
“…MRI g-ratios are derived by combining AVF measures from neurite orientation dispersion and density imaging and MVF from MTsat to provide an estimate of myelin thickness. A number of previous studies have identified an association between T 1 and magnetization transfer ratio values, 18 and myelin loss, including paired MRI–neuropathology studies. 18 , 19 Our analysis, however, found significant correlation between lesional g-ratio and elevated serum neurofilament, whereas MT and T 1 measures alone showed no such association with serum neurofilament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI g-ratios are derived by combining AVF measures from neurite orientation dispersion and density imaging and MVF from MTsat to provide an estimate of myelin thickness. A number of previous studies have identified an association between T 1 and magnetization transfer ratio values, 18 and myelin loss, including paired MRI–neuropathology studies. 18 , 19 Our analysis, however, found significant correlation between lesional g-ratio and elevated serum neurofilament, whereas MT and T 1 measures alone showed no such association with serum neurofilament.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have identified an association between T 1 and magnetization transfer ratio values, 18 and myelin loss, including paired MRI–neuropathology studies. 18 , 19 Our analysis, however, found significant correlation between lesional g-ratio and elevated serum neurofilament, whereas MT and T 1 measures alone showed no such association with serum neurofilament. The degree to which g-ratio may provide a more specific surrogate measure of demyelination in early RRMS, and how individual MT and diffusion measures reflect varying proportions of myelin and axonal damage, warrants further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Using computational models of biophysical properties of tissues, it is possible to derive metrics sensitive to microstructural integrity and metabolic information of the underlying tissue ( Granziera et al, 2021 ). Ultimately, the aim would be to provide patient-specific metrics able to predict outcomes and contribute to decision making on disease management ( Granziera et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…За даними німецьких дослідників, випадки РС у дітей віком до 10 та 15 років становлять 0,64 та 2,64 на 100 тис. населення відповідно [4].…”
Section: дніпровський медичний інститут традиційної і нетрадиційної медицини дніпро українаunclassified